2004
DOI: 10.1111/j.1651-2227.2004.tb02699.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between socio‐economic status and physical activity patterns in South African children

Abstract: Physical activity levels and socio-economic variables are closely related in this population of South African children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
74
5
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 22 publications
17
74
5
3
Order By: Relevance
“…Same study reported that there are no consciences on the criteria for determining abdominal obesity. It is reported that children who have mothers with college degree have higher activity levels (McVeigh et al, 2004). The same study also reported that low activity and more TV watching children groups have families from lower SES (McVeigh et al, 2004).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Same study reported that there are no consciences on the criteria for determining abdominal obesity. It is reported that children who have mothers with college degree have higher activity levels (McVeigh et al, 2004). The same study also reported that low activity and more TV watching children groups have families from lower SES (McVeigh et al, 2004).…”
Section: Discussionmentioning
confidence: 69%
“…It is reported that children who have mothers with college degree have higher activity levels (McVeigh et al, 2004). The same study also reported that low activity and more TV watching children groups have families from lower SES (McVeigh et al, 2004). On the other hand, Dorsey et al (2010).…”
Section: Discussionmentioning
confidence: 79%
“…Low socioeconomic status has been identified as a possible determinant of physical inactivity. [40][41][42][43] Recently, trials of interventions targeting socially disadvantaged people Identification of included studies provided some evidence of the potential of this strategy. A higher level of activity in males compared with females is consistently observed throughout childhood and adolescence and evidence also suggests that both sexes tend to become less active with increasing age.…”
Section: Intervention Approachesmentioning
confidence: 99%
“…5 Studies performed on small, local and regional samples of South African children suggest that the relatively high prevalence of obesity may be attributed in part to a decline in habitual physical activity, an increase in inactivity and sedentary lifestyles, associated with increasing urbanisation and improved socioeconomic status within households (assessed by the reliance on motorised transport). 8,13,19,27,32 Indeed, it has been reported that children with lower levels of lean body mass and higher body mass index (BMI) are spending more time watching television or using computers, instead of engaging in physical activity, sports or play. 3,12,15,27,39,53 Moreover, a national study undertaken in South African adolescents suggests that only 54.3% have physical education classes on their timetable, and of these only 52.8% engage in vigorous activity during class.…”
Section: Introductionmentioning
confidence: 99%
“…8,13,19,27,32 Indeed, it has been reported that children with lower levels of lean body mass and higher body mass index (BMI) are spending more time watching television or using computers, instead of engaging in physical activity, sports or play. 3,12,15,27,39,53 Moreover, a national study undertaken in South African adolescents suggests that only 54.3% have physical education classes on their timetable, and of these only 52.8% engage in vigorous activity during class. 33 Physical activity in childhood tracks into adulthood, thereby emphasising the need to address the lack of physical activity in children and youth.…”
Section: Introductionmentioning
confidence: 99%